Potensi Limbah Cair Industri Tapioka sebagai Media Pertumbuhan Starter Bakteri Asam Laktat Pediococcus pentosaceus E.1222 - WULAN, RAHAYU; MERYANDINI, ANJA; SUNARTI, TITI CANDRA (Departemen Biologi, Institut Pertanian Bogor, 2017)
Fermentation of Lactic Acid Bacteria (LAB) Pediococcus pentosaceus can improve the quality of food and its shelf life. Using commercial LAB specific media, de Man Rogosa and Sharpe (MRS) for growth on industrial scale application is not efficient. Tapioca wastewater (TW) still contains some of the nutrients needed for the growth of P. pentosaceus, but needs the enrichment of carbon sources (5% of glucose) and nitrogen sources (ammonium sulfate). This study aimed to use tapioca industrial wastewater with the addition of glucose and ammonium sulfate as an alternative growth media for lactic acid bacteria P. pentosaceus E.1222. The results showed that glucose and nitrogen had no significant effect on the number of bacterial colonies. The highest substrate efficiency was tapioca wastewater (86.81%), MRS broth (53.73%), and TW with 5% of glucose and 1% of ammonium sulfate (43.53%) respectively. Maximum growth rate (μmaks) was found in TW with 5% of glucose and 1% of ammonium sulfate (0,52 hours-1). Increasing the starter volume until 1000 mL in TW with 5% of glucose and 1% of ammonium sulfate showed a slight decrease in the log number of bacteria from 8,836 (50 mL), 8,401 (500 mL), to 8,063 (1000 mL).